EDEN ISS: Providing fresh food to overwintering Neumayer Station III crews and long duration space missions - Bamsey, Matthew; Zabel, Paul; Schubert, Daniel; Kohlberg, Eberhard; Mengedoht, Dirk (2016)
Provision of fresh produce to overwintering Antarctic crews is a challenge. The fact that at least 46 different greenhouses or plant production systems have existed at one time or another in Antarctica demonstrates the desire to produce food in-situ, even in this harsh environment. The EDEN ISS project will deploy an advanced plant growth system to Neumayer Station III. In addition to providing overwintering crews with fresh produce, the project aims to advance the technology readiness and operations techniques of space-based plant growth systems. The EDEN ISS ‘Mobile Test Facility’ is designed from two 20 ft shipping containers. These containers will be mounted upon an elevated platform situated approximately 300 m south of Neumayer Station III. The facility will be composed of three distinct sections; a cold porch; a Service Section, housing the bulk of the facility subsystems as well as a refrigerator-sized growth rack specifically designed to advance microgravity-based growth systems; and a Future Exploration Greenhouse providing the main plant production area of the facility. The greenhouse module will utilize multilevel growth systems and employ a number of advanced technologies such as LED lighting, aeroponic and nutrient-film technique irrigation systems, CO2 enrichment and air management equipment so as to limit overall power use and material requirements while maximizing the overall biomass output of the facility. The facility will ensure conformance to environmental protection regulations through the implementation of the lessons learned from past facilities and a number of specialized decontamination and monitoring techniques and technologies. The Mobile Test Facility is presently under manufacture and integration of its various subsystems will commence in late 2016. Following close to a year of testing and growth trials, the facility will arrive in Antarctica in late 2017 and undergo its first year of operations in which a number of additional scientific goals have been set. It is expected that the ...